Оценка параметров качества видеоконференцсвязи - Кадацкая, О. И.; Сабурова, С. А.; Тега, А. А. (ХНУРЕ, 2018)
The efficient QoS assessment of VoLTE service is a crucial item for LTE networks operators. Studies’ were built on simulation tools ,this study provided detailed methods to calculate the required parameters QoS.
Keywords: 4G; коммутация пакетов; голос; LTE; видео; мультимедийная информация; качество видеоконференцсвязи